Experimental study on the fire resistance of unprotected concrete-filled steel tubular columns under multi-loading. (March 2021) - Shintani, Yusuke; Nishimura, Toshihiko; Okazaki, Tomohito; Kinoshita, Takuya; Ito, Hidetoshi; Liew, J.Y. Richard
Abstract: This paper describes a series of four full-scale furnace tests conducted on unprotected concrete-filled steel tubular columns with and without reinforcement bars. Three of the columns were subjected to compression and horizontal loads, considering the end restraints provided by the adjacent cooler frame members and the forced displacement caused by thermal elongation of the heated beam during fire. One of the columns was subjected to concentric load for the purpose of benchmark comparison. The test setup consisted of multi-loaded specimens that comprised two-story columns which were subjected to compression load. The lower column was subjected to an ISO-834 standard fire and a displacement control horizontal force was applied to the top of the column until a horizontal displacement of 1/50th of the heating length of the column was attained after 2 or 4 h of fire. The test results showed that the failure times of the columns under multi-loading conditions were shorter than those of the columns under axial loading condition because of the double curvature bending on the core concrete. The double curvature bending was observed to be more severe than the single curvature bending in the eccentrically loaded furnace test. Highlights: Fire resistance of reinforced CFST columns under multi-loading was studied. Restraint by surrounding frame and forced displacement by heated beam were assessed. Additional bending action worsened fire resistance performance significantly.